Features of the formation of the root system of Crambe tataria Sebeόk in Western Kazakhstan - Turalin, B.A.; Kuprijanov, A.N.; Kurbatova, N.V.; Inelova, Z.A.; Kurmanbayeva, M.S.; Abidkulova К.Т.; Bazargaliyeva А.А.; Admanova, G.B.; Childibayeva, A.Zh. (Fundamental and Experimental Biology, 2022)
The morphology of root systems is paramount for a scientifically sound strategy for the conservation of rare and endangered plants. The morphology of the root system of Crambe tataria Sebeók, a rare and endangered plant listed in the Red Book of Kazakhstan, growing on the chalk hills of the Poduralsky Plateau in the valley of the Uilriver, was studied. Root systems were studied by the method of I.O. Baitulin separately for each age condition. At the first stages of its development, the root system develops ahead of time. In the immature state, a long rod-like low-branched root is formed, reaching 40 cm deep. In the virginal state, the roots reach a depth of 100–150 cm, have a diameter at the base of the socket 2–2.5(3) cm. According to the classification of root systems in adults, the root system is ombrophytic, it does not reach the groundwater level. The depth of penetration into the ground is average (up to 4 m). The spread of lateral roots is drooping or semi-drooping — the roots are directed downward at an angle of 45°. According to the density of branching of lateral roots (the ratio of the number of lateral roots of the first order to the length of the main root (pcs/cm) is rare (0.1 –0.5 pcs/cm) or weak 0.2–1.0 pcs/cm), the root system is rare and weakly branching.